Quantifying inequities in US federal response to hurricane disaster in Texas and Florida compared with Puerto Rico - Charley E Willison; Phillip M Singer; Melissa S Creary; Scott L. Greer (BMJ Global Health)
If disaster responses vary in their effectiveness across communities, health equity is affected. This paper aims to evaluate and describe variation in the federal disaster responses to 2017 Hurricanes Harvey, Irma and Maria, compared with the need and severity of storm damage through a retrospective analysis. Our analysis spans from landfall to 6 months after landfall for each hurricane. To examine differences in disaster responses across the hurricanes, we focus on measures of federal spending, federal resources distributed and direct and indirect storm-mortality counts. Federal spending estimates come from congressional appropriations and Federal Emergency Management Agency (FEMA) records. Resource estimates come from FEMA documents and news releases. Mortality counts come from National Oceanic and Atmospheric Administration (NOAA) reports, respective vital statistics offices and news articles. Damage estimates came from NOAA reports. In each case, we compare the responses and the severity at critical time points after the storm based on FEMA time logs. Our results show that the federal government responded on a larger scale and much more quickly across measures of federal money and staffing to Hurricanes Harvey and Irma in Texas and Florida, compared with Hurricane Maria in Puerto Rico. The variation in the responses was not commensurate with storm severity and need after landfall in the case of Puerto Rico compared with Texas and Florida. Assuming that disaster responses should be at least commensurate to the degree of storm severity and need of the population, the insufficient response received by Puerto Rico raises concern for growth in health disparities and increases in adverse health outcomes.